Oblicz wartość wyrażenia x2(x do kwadratu)-5x+3
1)x=pierwiastek z 7 +4
2)x=2 pierwiastek z 3 -5
3)x=4 pierwiastek z 2-1
4)x=2-3 pierwiastek z 2



Odpowiedź :

Odpowiedź:

[tex](a-b)^2=a^2-2ab+b^2\\(a+b)^2=a^2+2ab+b^2[/tex]

Szczegółowe wyjaśnienie:

1. [tex](\sqrt{7} +4)^2-5(\sqrt{7}+4)+3=7+8\sqrt{7}+16-5\sqrt{7}-20+3= 6+3\sqrt{7}[/tex]

2. [tex](2\sqrt{3}-5)^2 - 5*(2\sqrt{3}-5)+3=12-20\sqrt{3} +25-10\sqrt{3} +25+3= 65-30\sqrt{3}[/tex]

3. [tex](4\sqrt{2}-1)^2-5*(4\sqrt{2}-1)+3= 32-8\sqrt{2}+1-20\sqrt{2} +5+3= 41- 28\sqrt{2}[/tex]

4. [tex](2-3\sqrt{2})^2-5*(2-3\sqrt{2})+3=4-12\sqrt{2} +18-10+15\sqrt{2} +3=15+3\sqrt{2}[/tex]